1996
DOI: 10.1179/bjo.23.3.269
|View full text |Cite
|
Sign up to set email alerts
|

Aligning Archwires, the Shape of Things to Come?—A Fourth and Fifth Phase of Force Delivery

Abstract: Recent developments in material science have lent themselves to improving orthodontic archwire technology. The pace of change has been great, leaving the clinician a bewildering choice of materials for the purposes of force application. The following article characterises the properties of new archwire formulations and is intended to give guidance in choosing archwire material during the first stage of orthodontic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
7

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 19 publications
0
24
1
7
Order By: Relevance
“…Brauchli, et al 8 (2011) found Af of 29.2°C for archwire NeoSentalloy size 0.016"x0.022". Conversely, Evans and Durning 10 (1996) observed Af of 68°C and Mf of 24°C for archwire Heat Activated NiTi size 0.016"x0.022", which disagrees with this study. The present results suggest that these two archwires present the best clinical performance considering the shape memory effect and pseudoelasticity property, since the Af of these archwires is closer to the oral temperature.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Brauchli, et al 8 (2011) found Af of 29.2°C for archwire NeoSentalloy size 0.016"x0.022". Conversely, Evans and Durning 10 (1996) observed Af of 68°C and Mf of 24°C for archwire Heat Activated NiTi size 0.016"x0.022", which disagrees with this study. The present results suggest that these two archwires present the best clinical performance considering the shape memory effect and pseudoelasticity property, since the Af of these archwires is closer to the oral temperature.…”
Section: Discussioncontrasting
confidence: 95%
“…Conversely, Figueiredo, et al 11 (2012) compared the mechanical behavior of the same archwires, except for the Heat Activated NiTi, and revealed that these archwires present pseudoelasticity. Evans and Durning 10 (1996) found Af of 24°C for the archwire Thermomemoria (Leone, Oxnard, CA, USA), suggesting similar clinical performance as the aforementioned archwires.…”
Section: Discussionmentioning
confidence: 97%
“…(1992) in order that the desired clinical characteristics could be obtained. Evans & Durning (1996) reported the differences in formulations of nickel-titanium alloy and their applications in archwire technology. A review article published by Kusy (1997) described the properties and characteristics of contemporary archwires from initial development to their current use in variable modulus orthodontics as advocated by Burstone (1981).…”
Section: Orthodonticsmentioning
confidence: 99%
“…7 Multistranded stainless steel and nickel titanium alloys seem to be the closest archwire materials fulfilling these requirements. [8][9][10][11] Though nickel titanium (NiTi) alloy-based wires are most commonly used during the leveling and aligning phase of treatment, 12 multistranded wires are proposed as an alternative to these wires based on classic mechanics theory (Strength 5 Stiffness 3 Range), 13 and over the decades, it has proved to be equally efficient as NiTi alloy-based wires. [14][15][16] Though NiTi archwires have wide acceptance in orthodontics because of their low load-deflection ratio and better control of force magnitude, many authors 17,18 have expressed the need for clinical performance evaluation of these wires because their properties have not been assessed in clinical studies to the same extent as have their mechanical properties in the laboratory setup.…”
Section: Introductionmentioning
confidence: 99%